N-octane aromatization hierarchical pore structure catalyst as well as preparation method and application thereof
By loading metal ZSM-5 molecular sieve on the surface of the multi-stage pore three-dimensional nanosheet ZSM-5 molecular sieve, forming a multi-stage pore structure Zn modified ZSM-5 molecular sieve catalyst, the selectivity of existing catalysts in the catalytic reforming of aromatic hydrocarbons and alkane aromatization process is solved. The problem of low and prone to carbon deposits leads to inactivation, achieving higher aromatic selectivity and catalyst stability, and is suitable for industrial production.
Patent Information
- Application Number
- CN202411461118.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-25
AI Technical Summary
The existing ZSM-5 molecular sieve catalysts have problems such as low aromatic selectivity and catalysts prone to carbon deposits and inactivation during aromatic hydrocarbon catalytic reforming and alkane aromatization, which cannot meet industrial needs.
By loading metal Zn on the surface of the multi-stage pore three-dimensional nanosheet ZSM-5 molecular sieve, a multi-stage pore structure Zn modified ZSM-5 molecular sieve catalyst is formed, and Zn elements are introduced by an equal volume impregnation method to improve the aromatic selectivity and stability of the catalyst.
The catalyst exhibits higher aromatic selectivity in n-octane aromatization reaction, with a total aromatic selectivity of up to 70%, of which light aromatics account for more than 80%, and the process is simple and easy to use, suitable for industrialization Production.
Smart Images

Figure CN119500240A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of industrial catalysis, and in particular to a n-octane aromatization multi-level pore structure catalyst and a preparation method and application thereof. Background Art
[0002] Aromatic hydrocarbons, mainly benzene, toluene, and xylene (BTX for short), are important organic chemical raw materials after ethylene and propylene. Since BTX derivatives are widely used in the production of chemical products and fine chemicals such as fuels, petrochemicals, chemical fibers, plastics and rubber, the market demand for aromatic hydrocarbons has continued to grow in recent years. In particular, as the world's oil resources become increasingly scarce, the price of BTX remains high. Catalytic reforming and alkane aromatization processes are the main sources of light aromatic hydrocarbons. ZSM-5 molecular sieve is widely used as an aromatization catalyst in various aromatization reactions due to its excellent shape-selective catalytic ability. Although the ZSM-5 molecular sieve catalyst has good aromatization catalytic activity, it still cannot meet industrial needs due to the low selectivity of aromatic hydrocarbons in its products and the problem of catalyst coking and deactivation caused by carbon deposition reactions on the acidic sites on the molecular sieve surface.
[0003] In order to improve the yield of aromatics and the life of the catalyst, metals such as zinc and silver are usually used to modify the ZSM-5 molecular sieve. Among the metals used for modification reported in the literature, zinc is relatively cheap and has high catalytic activity, which can improve the yield of aromatics. However, the commonly used ZSM-5 molecular sieves are all micron-sized grains with long micropores, which are not conducive to the diffusion of aromatic products, and are prone to further reaction of aromatics to form carbon deposition, resulting in catalyst deactivation.
[0004] Therefore, seeking a simple, efficient and easy-to-industrial production method for preparing hierarchical Zn-modified ZSM-5 molecular sieves has important application value for designing and synthesizing aromatization catalytic materials with high catalytic activity and high selectivity. Summary of the invention
[0005] In view of this, the present invention provides a n-octane aromatization multi-level pore structure catalyst and a preparation method and application thereof. The catalyst has higher n-octane aromatization performance and can inhibit further aromatization on the catalyst surface.
[0006] The technical solution provided by the present invention is specifically:
[0007] In the first aspect, the present invention provides a hierarchical porous structure catalyst for the aromatization of n-octane, wherein the catalyst uses a hierarchical porous three-dimensional nanosheet ZSM-5 molecular sieve as a carrier and metal Zn as an aromatization metal component, which is loaded on the surface of the molecular sieve, wherein the loading amount of the metal Zn is 0.1% to 10% by mass.
[0008] In a second aspect, the present invention further provides a method for preparing the catalyst, comprising:
[0009] 1) mixing and stirring a silicon source, an aluminum source, an alkali source, an organic surfactant soft template, a seed crystal and an organic amine auxiliary agent in sequence to form a mixed gel, and then subjecting the mixed gel to a hydrothermal crystallization reaction, filtering, washing, drying and calcining the obtained crystallized product, and finally obtaining a hierarchical pore three-dimensional nanosheet ZSM-5 molecular sieve;
[0010] 2) Metal Zn is introduced into the surface of the hierarchical porous three-dimensional nanosheet ZSM-5 molecular sieve by an equal volume impregnation method, and finally a hierarchical porous three-dimensional nanosheet Zn-modified ZSM-5 molecular sieve is obtained, which is a hierarchical porous structure catalyst for n-octane aromatization.
[0011] Preferably, the equal volume impregnation method:
[0012] Weigh a Zn salt and dissolve it in deionized water to obtain a zinc solution as a metal element precursor solution, and add the zinc solution dropwise into the carrier. The temperature of the equal volume impregnation process is 10-80° C., the stirring time is 5-120 min, and the ultrasonic treatment time is 5-120 min. Drying includes at least one of vacuum drying and forced air drying, the drying temperature is 50-120° C., and the drying time is 3-12 h. The roasting temperature is 400-650° C., and the roasting time is 1-10 h.
[0013] Preferably, the organic amine auxiliary agent is a mixture of at least one or more of methylamine, ethylamine, ethylenediamine, triethylamine, n-propylamine, n-butylamine, tert-butylamine, hexylamine, hexyldiamine, trioctylamine, dodecylamine, hexadecylamine and octadecylamine;
[0014] The seed crystal is a conventional ZSM-5 molecular sieve with a silicon-aluminum ratio of 100;
[0015] The alkaline source is at least one or more mixtures of sodium hydroxide, potassium hydroxide, magnesium hydroxide and barium hydroxide;
[0016] The silicon source is one of sodium silicate, silicic acid, silica sol, fumed silica, white carbon black, methyl orthosilicate, tetraethyl orthosilicate, or a dual silicon source system;
[0017] The aluminum source is a mixture of one or more of sodium aluminate, aluminum isopropoxide, aluminum sulfate, aluminum chloride, aluminum nitrate, aluminum hydroxide, boehmite, pseudoboehmite, and pseudoboehmite.
[0018] Preferably, the organic surfactant soft template is a long-chain asymmetric gemini quaternary ammonium salt surfactant;
[0019] The molar composition of the alkali source, aluminum source, silicon source, gemini quaternary ammonium salt surfactant and organic amine auxiliary agent is: Na2O:Al2O3:SiO2:R:H2O:X is 1-30:0-2:100:0-10:1000-6000:0-5, wherein R represents the gemini quaternary ammonium salt surfactant and X represents the organic amine auxiliary agent.
[0020] Preferably, the Zn salt is one or more of nitrate, sulfate, carbonate, and halide, and the concentration of the metal element precursor solution is 0.01-50 mg / mL.
[0021] Finally, the present invention also provides the application of the above-mentioned n-octane aromatization multi-level pore structure catalyst, which is applied to the n-octane aromatization reaction to produce aromatics.
[0022] Preferably, the application method comprises: tabletting, crushing and screening the n-octane aromatization multi-level porous structure catalyst into particles of 40 to 60 mesh, then loading the obtained particles into a continuous flow fixed bed reactor, and activating the particles with nitrogen at 380 to 500° C. for half an hour before the reaction starts; pumping the raw material n-octane into the fixed bed reactor with a horizontal flow pump, and reacting under the conditions of an operating pressure of 0.1 MPa, a reaction temperature of 400 to 700° C., and a raw material liquid space velocity of 0.2 to 4.0 h; and monitoring the outlet gas of the fixed bed reactor online with a gas chromatograph to obtain a gas phase product mainly containing various light hydrocarbons and light aromatics of C1 to C5.
[0023] The present invention provides a catalyst for n-octane aromatization with a multi-level pore structure, a preparation method and an application thereof, wherein the catalyst
[0024] The multi-level pore structure catalyst loads the active metal Zn element on the surface of the multi-level pore three-dimensional nanosheet ZSM-5 molecular sieve, which can provide acid sites and aromatization sites for n-octane to generate aromatics. The multi-level pore structure catalyst prepared by the present invention has a ZSM-5 molecular sieve with a nano-layered structure, a short diffusion path within the molecular sieve crystal, and a large specific surface area. The high-value light aromatics generated on the catalyst are further aromatized to generate heavy aromatics.
[0025] In addition, the multi-level pore structure catalyst also has good n-octane aromatization performance, and the total aromatics selectivity in the product can reach 70%, of which light aromatics account for more than 80%.
[0026] Finally, in the preparation method of the present invention, the raw materials used are easily available, the production process is simple, the performance is excellent, and it is suitable for industrial production.
[0027] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0030] Figure 1 XRD spectrum of the sample of Example 1 of the present invention;
[0031] Figure 2 SEM image of the sample of Example 1 of the present invention;
[0032] Figure 3 SEM image of the sample of Example 2 of the present invention;
[0033] Figure 4 SEM image of the sample of Example 3 of the present invention;
[0034] Figure 5 TEM images of samples of Examples 1, 2, and 3 of the present invention;
[0035] Figure 6 XRD spectrum of comparative sample;
[0036] Figure 7 The performance results of the n-octane aromatization reaction of the sample in Example 1 of the present invention;
[0037] Figure 8 The performance results of the n-octane aromatization reaction of the sample in Example 2 of the present invention;
[0038] Fig. 9 The performance results of the n-octane aromatization reaction of the sample in Example 3 of the present invention;
[0039] Fig.10 The aromatization reaction performance of n-octane of the comparative example sample of the present invention. DETAILED DESCRIPTION
[0040] The present invention is further explained below in conjunction with specific implementation modes, but it is not intended to limit the protection scope of the present invention.
[0041] In order to obtain an aromatization catalytic material with high catalytic activity and high selectivity, firstly, this embodiment provides a n-octane aromatization multi-level porous structure catalyst, the catalyst carrier is a multi-level porous three-dimensional nanosheet ZSM-5 molecular sieve, the aromatization metal component is Zn element, which is introduced into the surface of the multi-level porous three-dimensional nanosheet ZSM-5 molecular sieve by an equal volume impregnation method; in terms of mass percentage, the metal Zn is 0.1% to 10%;
[0042] In a second aspect, this embodiment also provides a method for preparing the above catalyst, comprising:
[0043] A certain amount of silicon source, aluminum source, alkali source, gemini quaternary ammonium salt surfactant, seed crystal and organic amine additive are mixed and stirred evenly to form an initial mixed gel for molecular sieve synthesis, and then the mixed gel is transferred to a stainless steel crystallization kettle lined with polytetrafluoroethylene, hydrothermally crystallized for a period of time, and the crystallized product is filtered, washed, dried and calcined to obtain a multi-level porous three-dimensional nanosheet ZSM-5 molecular sieve;
[0044] A certain mass of zinc salt is weighed and dissolved in deionized water, and the zinc solution is added dropwise into a carrier, and introduced into the surface of a multi-level porous three-dimensional nanosheet ZSM-5 molecular sieve by an equal volume impregnation method; the temperature of the equal volume impregnation process is 10-80°C, the stirring time is 5-120 minutes, and the ultrasonic treatment time is 5-120 minutes; the drying includes at least one of vacuum drying and blast drying, the drying temperature is 50-120°C, and the drying time is 3-12 hours; the roasting temperature is 400-650°C, and the roasting time is 1-10 hours.
[0045] Preferably, the preparation method of the gemini quaternary ammonium salt surfactant comprises: adding bromoalkane and N,N,N,N-tetramethyl-1,6-hexanediamine to a mixed solvent of toluene and acetonitrile, reacting at 80°C for 12 hours, cooling to room temperature, concentrating by rotary evaporation, filtering, and repeatedly washing the filter cake with anhydrous ether. The filter cake is placed in a vacuum oven and dried for 24 hours to obtain C 18-6-0 . Weigh a certain amount of C 18-6-0 and 1-bromohexane, added into a round-bottom flask containing 100 mL of acetonitrile, refluxed at 80°C for 12 h, cooled, filtered, repeatedly washed with anhydrous ether, and the filter cake was vacuum dried for 24 h to obtain a gemini quaternary ammonium surfactant.
[0046] The above method specifically comprises the following steps:
[0047] Step 1: adding an organic surfactant soft template and an alkali source to deionized water and stirring to obtain a solution A;
[0048] Step 2: Add silicon source to solution A and stir evenly to form solution B;
[0049] Step 3: dissolving an aluminum source in deionized water to obtain a C solution;
[0050] Step 4: adding solution C to solution B, stirring evenly, adding an organic amine auxiliary agent thereto, stirring until evenly added with seed crystals, continuing to stir evenly to form a mixed gel, and then subjecting the mixed gel to a hydrothermal crystallization reaction, filtering, washing, drying and calcining the obtained crystallized product to obtain a sodium-type multi-level porous three-dimensional nanosheet ZSM-5 molecular sieve;
[0051] Step 5: exchanging the sodium-type hierarchical pore three-dimensional nanosheet ZSM-5 molecular sieve with ammonium in an ammonium nitrate solution, filtering, washing, and calcining to obtain the hydrogen-type hierarchical pore three-dimensional nanosheet ZSM-5 molecular sieve;
[0052] Step 6: Introduce metallic Zn onto the surface of hydrogen-type hierarchical porous three-dimensional nanosheet ZSM-5 molecular sieve by an equal volume impregnation method, and finally obtain hierarchical porous three-dimensional nanosheet Zn-modified ZSM-5 molecular sieve.
[0053] In the preparation process of the hierarchical nano ZSM-5 molecular sieve, the molar composition of the reaction raw materials in the mixed gel is: Na2O: Al2O3: SiO2: R: H2O: X is 1-30: 0-2: 100: 0-10: 1000-6000: 0-5, wherein R represents a gemini quaternary ammonium salt surfactant, and X represents an organic amine auxiliary agent.
[0054] In the above synthesis system, the organic gemini quaternary ammonium salt surfactant not only acts as a template to induce the formation of ZSM-5 molecular sieve micropores, but also acts as a soft template to form the multi-level porous ZSM-5 molecular sieve mesoporous structure. n H 2n+1 -N + (CH3)2-C6H 12 -N + (CH3)2-C6H 13 ]Br2 (abbreviated as C n-6-6 , wherein n=10-22), wherein preferably C n-6-6 , where n=16~20.
[0055] The above-mentioned organic amine additive plays a role in regulating the morphology of the multi-level porous nano ZSM-5 molecular sieve aggregates. The organic amine additives used are at least one or more mixtures of methylamine, ethylamine, ethylenediamine, triethylamine, n-propylamine, n-butylamine, tert-butylamine, diethylenetriamine, hexylamine, hexyldiamine, trioctylamine, dodecylamine, hexadecylamine, and octadecylamine, wherein the organic amine additives are preferably ethylenediamine, triethylamine, diethylenetriamine, hexyldiamine, and the like.
[0056] The silicon source can be one or a dual silicon source system of water glass, silicic acid, silica sol, fumed silica, white carbon, methyl orthosilicate, and tetraethyl orthosilicate, wherein the preferred silicon source is fumed silica, silica sol, and tetraethyl orthosilicate.
[0057] The aluminum source can be a mixture of one or more of sodium aluminate, aluminum isopropoxide, aluminum sulfate, aluminum chloride, aluminum nitrate, aluminum hydroxide, boehmite, pseudoboehmite, and pseudoboehmite, wherein the preferred aluminum source is aluminum isopropoxide, aluminum sulfate, and pseudoboehmite.
[0058] The alkali source may be a mixture of one or more of sodium hydroxide, potassium hydroxide, magnesium hydroxide or calcium hydroxide, wherein the alkali source is preferably sodium hydroxide.
[0059] According to the preparation method provided by the present invention, the physicochemical properties such as the silicon-to-aluminum ratio, grain morphology, pore structure and acid properties of the multi-level porous nano ZSM-5 molecular sieve aggregates can be flexibly adjusted by adjusting the type and amount of the organic amine added to the synthesis system and the preparation parameters such as the alkalinity, water content, silicon source, aluminum source and crystallization temperature and crystallization time of the synthesis system, thereby adjusting its catalytic performance and application field.
[0060] Preferably, the isovolumetric impregnation parameters are: weigh a certain mass of zinc salt and dissolve it in deionized water, add the zinc solution dropwise to the carrier and continue stirring for 20 minutes, then ultrasonically treat the mixed sample for 10 minutes, transfer it to a 40°C oven, and dry it overnight. Then, calcine at 550°C for 4 hours in an air atmosphere to obtain a hierarchical pore three-dimensional nanosheet Zn-modified ZSM-5 molecular sieve.
[0061] Finally, this embodiment also provides an application of a multi-level pore structure catalyst for n-octane aromatization, which is used for the n-octane aromatization reaction to produce aromatics.
[0062] The process of carrying out oxygen-free aromatization of n-octane using a multi-level porous three-dimensional nanosheet ZSM-5 molecular sieve catalyst comprises the following steps:
[0063] (1) The prepared catalyst is tableted, crushed, and sieved into particles of 40 to 60 mesh, and then the obtained particles are loaded into a continuous flow fixed bed reactor and activated with nitrogen at 380 to 500° C. for half an hour;
[0064] (2) using a horizontal flow pump to pump the raw material n-octane into a fixed bed reactor, and reacting under the conditions of an operating pressure of 0.1 MPa, a reaction temperature of 400 to 700° C., and a raw material liquid space velocity of 0.2 to 4.0 h;
[0065] (3) The outlet gas of the fixed bed reactor is monitored online by a gas chromatograph, and the gas phase products mainly contain various light hydrocarbons of C1 to C5 and aromatic products mainly contain light aromatics such as benzene, toluene and xylene.
[0066] The multi-level porous three-dimensional nanosheet ZSM-5 molecular sieve prepared by the present invention has high aromatics selectivity and good catalyst stability.
[0067] The present invention simultaneously adds a gemini quaternary ammonium salt surfactant and an organic amine in a hydrothermal synthesis system, and realizes the controllable preparation of a multi-level pore nano ZSM-5 molecular sieve in a one-step method. The organic gemini quaternary ammonium salt surfactant not only serves as a template agent for inducing the formation of micropores of the ZSM-5 molecular sieve, but also serves as a soft template agent for forming the multi-level pore ZSM-5 molecular sieve, and the organic amine additive plays a role in regulating the morphology of the ZSM-5 molecular sieve.
[0068] The present invention is further explained below in conjunction with specific embodiments, but is not intended to limit the protection scope of the present invention.
[0069] Example 1
[0070] 0.4 g of gemini quaternary ammonium salt surfactant C 18-6-6 and 0.15g of sodium hydroxide were added to 3.0g of deionized water, and stirred in a constant temperature water bath at 60°C for 2h to form a solution A; then 5.2g of tetraethyl orthosilicate was added dropwise to the solution A, and the mixture was stirred in a constant temperature water bath at 60°C for 2h to form a solution B; then 0.1g of aluminum isopropoxide was added to 18g of deionized water, and stirred in a constant temperature water bath at 60°C until completely dissolved to form a solution C; the solution C was added dropwise to the solution B, and the mixture was stirred for 12h until it was completely uniform; then 0.075g of a ZSM-5 molecular sieve with a silicon-aluminum ratio of 100 was added, and the mixture was stirred for 2h; the mixture was transferred to a stainless steel crystallization kettle lined with polytetrafluoroethylene, and crystallized at 150°C for 4d; the obtained product was filtered and dried to obtain a molecular sieve raw powder.
[0071] The original molecular sieve powder was placed in a muffle furnace and calcined at 550°C for 6 hours to remove the template agent, thereby obtaining a sodium-type multi-level porous three-dimensional nanosheet ZSM-5 molecular sieve.
[0072] Then, the sodium-type multi-level porous three-dimensional nanosheet ZSM-5 molecular sieve was continuously ammonium exchanged three times in a 1M ammonium nitrate solution, filtered, washed, and calcined at 550° C. for 4 hours to obtain the hydrogen-type multi-level porous three-dimensional nanosheet ZSM-5 molecular sieve.
[0073] Finally, 0.0671 g of zinc nitrate was weighed and dissolved in 1 ml of deionized water to obtain a zinc solution as a metal element precursor solution. The zinc solution was added dropwise into the hydrogen-type multi-level porous three-dimensional nanosheet ZSM-5 molecular sieve carrier, and after drying and calcination, a multi-level porous three-dimensional nanosheet Zn-modified ZSM-5 molecular sieve catalyst was obtained.
[0074] like Figure 1As shown, the prepared multi-level porous nano ZSM-5 molecular sieve sample was analyzed by XRD, and it was found that it had a typical MFI topological structure, and the molecular sieve sample had high crystallinity and purity, good quality, and an obvious diffraction peak broadening phenomenon, indicating that the synthesized ZSM-5 molecular sieve had a small grain size.
[0075] Example 2
[0076] 0.4 g of gemini quaternary ammonium surfactant C18-6-6 and 0.15 g of sodium hydroxide were added to 3.0 g of deionized water, and stirred in a constant temperature water bath at 60° C. for 2 h to form a solution A; then 5.2 g of tetraethyl orthosilicate was added dropwise to the solution A, and the solution was stirred in a constant temperature water bath at 60° C. for 2 h to form a solution B; then 0.1 g of aluminum isopropoxide was added to 18 g of deionized water, and stirred in a constant temperature water bath at 60° C. until it was completely dissolved to form a solution C; the solution C was added dropwise to the solution B, and the stirring was continued for 12 h; then 2.5 g of triethylamine solution was added, and the stirring was continued until uniform; then 0.075 g of a seed crystal with a silicon-aluminum ratio of 100 ZSM-5 molecular sieve was added, and the stirring was continued for 2 h; the mixture was transferred to a stainless steel crystallization kettle lined with polytetrafluoroethylene, and crystallized at 150° C. for 4 d; the obtained product was filtered and dried to obtain a molecular sieve raw powder.
[0077] The original molecular sieve powder was placed in a muffle furnace and calcined at 550°C for 6 hours to remove the template agent, thereby obtaining a sodium-type multi-level pore three-dimensional nanosheet ZSM-5 molecular sieve. Then, the sodium-type multi-level pore three-dimensional nanosheet ZSM-5 molecular sieve was continuously ammonium exchanged three times in a 1M ammonium nitrate solution, filtered, washed, and calcined at 550°C for 4 hours to obtain a hydrogen-type multi-level pore three-dimensional nanosheet ZSM-5 molecular sieve.
[0078] Finally, 0.0671 g of zinc nitrate was weighed and dissolved in 1 ml of deionized water to obtain a zinc solution as a metal element precursor solution. The zinc solution was added dropwise into the hydrogen-type multi-level porous three-dimensional nanosheet ZSM-5 molecular sieve carrier, and after drying and calcination, a multi-level porous three-dimensional nanosheet Zn-modified ZSM-5 molecular sieve catalyst was obtained. Figure 8 The performance results of the n-octane aromatization reaction of Example 2 show that when the reaction temperature is higher than 550° C., the n-octane conversion rate reaches more than 99%, indicating that the n-octane can be completely converted and the BTX selectivity reaches 83%.
[0079] Example 3
[0080] 0.4 g of gemini quaternary ammonium surfactant C18-6-6 and 0.15 g of sodium hydroxide were added to 3.0 g of deionized water, and stirred in a constant temperature water bath at 60° C. for 2 h to form a solution A; then 5.2 g of tetraethyl orthosilicate was added dropwise, and the mixture was stirred in a constant temperature water bath at 60° C. for 2 h to form a solution B; then 0.1 g of aluminum isopropoxide was added to 18 g of deionized water, and stirred in a constant temperature water bath at 60° C. until completely dissolved to form a solution C; the solution C was added dropwise to the solution B, and stirring was continued for 12 h; then 2.5 g of diethylenetriamine solution was added, and stirring was continued until uniform; then 0.075 g of a seed crystal with a silicon-aluminum ratio of 100 ZSM-5 molecular sieve was added, and stirring was continued for 2 h; the mixture was transferred to a stainless steel crystallization kettle lined with polytetrafluoroethylene, and crystallized at 150° C. for 4 d; the obtained product was filtered and dried to obtain a molecular sieve raw powder. The original molecular sieve powder was placed in a muffle furnace and calcined at 550°C for 6 hours to remove the template agent, thereby obtaining a sodium-type multi-level pore three-dimensional nanosheet ZSM-5 molecular sieve. Then, the sodium-type multi-level pore three-dimensional nanosheet ZSM-5 molecular sieve was continuously ammonium exchanged three times in a 1M ammonium nitrate solution, filtered, washed, and calcined at 550°C for 4 hours to obtain a hydrogen-type multi-level pore three-dimensional nanosheet ZSM-5 molecular sieve.
[0081] Finally, 0.0671 g of zinc nitrate was weighed and dissolved in 1 ml of deionized water to obtain a zinc solution as a metal element precursor solution. The zinc solution was added dropwise into the hydrogen-type multi-level porous three-dimensional nanosheet ZSM-5 molecular sieve carrier, and after drying and calcination, a multi-level porous three-dimensional nanosheet Zn-modified ZSM-5 molecular sieve catalyst was obtained. Fig. 9 The n-octane aromatization result of Example 3 shows that when the reaction temperature is higher than 550° C., the n-octane conversion rate reaches more than 99%, indicating that the n-octane can be completely converted and the BTX selectivity reaches 77%.
[0082] Before the catalyst is loaded into the reaction tube, the raw powder is tableted, crushed and sieved to obtain catalyst particles of 40-60 mesh.
[0083] Weigh 0.75g of multi-level porous nano Zn modified ZSM-5 molecular sieve catalyst, put it in a stainless tube reaction tube, then adjust the volume flow rate of diluent nitrogen to 400mL / min, and start heating after continuous introduction for 0.5h. After the temperature in the reaction tube stabilizes to the reaction temperature, introduce 2ml / h of raw material n-octane, and after being gasified by the preheating section at the upper end of the reaction tube, it is contacted with the catalyst bed to undergo catalytic cracking reaction, collect the reaction products online, and analyze the product composition and content by gas chromatography. The reaction temperature range is 400-650℃. "BTX" represents the total yield of benzene, toluene and xylene.
[0084] like Figure 2-Figure 4 It can be seen that the morphology of ZSM-5 molecular sieve nanocrystals varies with the different organic amine additives. Figure 2 It can be observed that the multi-level porous nano ZSM-5 molecular sieve (Example 1) formed without adding organic amine additives has a grain size of about 1.5 μm, and its secondary assembly unit is a nanorod-shaped crystal; Figure 3 It can be seen that the secondary assembly unit of the hierarchical ZSM-5 molecular sieve aggregate synthesized with triethylamine organic additive is a nanosheet with a thickness of about 6nm, which is then further self-assembled to form microspherical crystals of about 4μm; Figure 4 It can be seen that the secondary assembly units of the multi-level porous ZSM-5 molecular sieve synthesized with diethylenetriamine organic additive are nanorod-like crystals with a diameter of about 15nm, and hollow elliptical crystals formed by the self-assembly of nanorods. From the nitrogen adsorption experiment, it can be seen that all prepared ZSM-5 molecular sieve samples have a mesoporous structure, which is a meso-microporous composite multi-level pore structure, and the mesopores may be the stacked intercrystalline mesopores formed in the process of ZSM-5 molecular sieve nanocrystals assembling to form aggregates. Figure 5 It can be seen that all prepared ZSM-5 zeolite sample catalysts have an obvious layered structure, and the distribution of Zn species on the catalyst is more uniform. Figure 7 The performance results of the n-octane aromatization reaction of Example 1 show that when the reaction temperature is higher than 550° C., the n-octane conversion rate reaches more than 99%, indicating that the n-octane can be completely converted and the BTX selectivity reaches 71%.
[0085] Table 1 Texture properties of samples of the present invention
[0086]
[0087] Comparative Example
[0088] Conventional ZSM-5 molecular sieve catalyst was purchased from Nankai Catalyst Factory, with a silicon-aluminum ratio SiO2 / Al2O3 of 100. The method for aromatization of n-octane using the catalyst is substantially the same as that in Example 1. "BTX" stands for benzene, toluene, and xylene. Figure 6 : is the XRD spectrum of the comparative example, which has characteristic diffraction peaks of a typical MFI framework structure. Fig.10 The aromatization result of n-octane in the comparative example shows that the highest BTX selectivity is 33%.
[0089] Those skilled in the art will readily appreciate other embodiments of the present invention after considering the specification and practicing the invention disclosed herein. This application is intended to cover any variations, uses or adaptations of the present invention that follow the general principles of the present invention and include common knowledge or customary techniques in the art that are not disclosed by the present invention. The specification and examples are to be considered exemplary only, and the true scope and spirit of the present invention are indicated by the following claims.
[0090] It should be understood that the present invention is not limited to what has been described above and that various modifications and changes may be made without departing from its scope. The scope of the present invention is limited only by the appended claims.
Claims
1. A catalyst for n-octane aromatization with a multi-level pore structure, characterized in that: The catalyst uses a multi-level porous three-dimensional nanosheet ZSM-5 molecular sieve as a carrier and metal Zn as an aromatization metal component loaded on the surface of the molecular sieve, wherein the loading amount of the metal Zn is 0.1% to 10% by mass.
2. A method for preparing the catalyst as claimed in claim 1, characterized in that: include: Step 1: adding an organic surfactant soft template and an alkali source to deionized water and stirring to obtain a solution A; Step 2: Add silicon source to solution A and stir evenly to form solution B; Step 3: dissolving an aluminum source in deionized water to obtain a C solution; Step 4: adding solution C to solution B, stirring evenly, adding an organic amine auxiliary agent thereto, stirring until evenly added with seed crystals, continuing to stir evenly to form a mixed gel, and then subjecting the mixed gel to a hydrothermal crystallization reaction, filtering, washing, drying and calcining the obtained crystallized product to obtain a sodium-type multi-level porous three-dimensional nanosheet ZSM-5 molecular sieve; Step 5: exchanging the sodium-type hierarchical pore three-dimensional nanosheet ZSM-5 molecular sieve with ammonium in an ammonium nitrate solution, filtering, washing, and calcining to obtain the hydrogen-type hierarchical pore three-dimensional nanosheet ZSM-5 molecular sieve; Step 6: Introduce metallic Zn onto the surface of hydrogen-type hierarchical porous three-dimensional nanosheet ZSM-5 molecular sieve by an equal volume impregnation method, and finally obtain hierarchical porous three-dimensional nanosheet Zn-modified ZSM-5 molecular sieve.
3. The method for preparing the catalyst according to claim 2, characterized in that: Step 6 Medium Volume Dip Method: Weigh a Zn salt and dissolve it in deionized water to obtain a zinc solution as a metal element precursor solution, and add the zinc solution dropwise into a hydrogen-type multi-level porous three-dimensional nanosheet ZSM-5 molecular sieve, wherein the temperature of the equal volume impregnation process is 10-80°C, the stirring time is 5-120 minutes, and the ultrasonic treatment time is 5-120 minutes; the drying includes at least one of vacuum drying and forced air drying, the drying temperature is 50-120°C, and the drying time is 3-12 hours; the roasting temperature is 400-650°C, and the roasting time is 1-10 hours.
4. The method for preparing the catalyst according to claim 2, characterized in that: The organic amine auxiliary agent is at least one or more mixtures of methylamine, ethylamine, ethylenediamine, triethylamine, n-propylamine, n-butylamine, tert-butylamine, hexylamine, hexyldiamine, trioctylamine, dodecylamine, hexadecylamine and octadecylamine; The seed crystal is a ZSM-5 molecular sieve with a silicon-aluminum ratio of 50-200; The alkali source is at least one or more mixtures of sodium hydroxide, potassium hydroxide, magnesium hydroxide and barium hydroxide. The silicon source is one of sodium silicate, silicic acid, silica sol, fumed silica, white carbon black, methyl orthosilicate, tetraethyl orthosilicate, or a dual silicon source system; The aluminum source is a mixture of one or more of sodium aluminate, aluminum isopropoxide, aluminum sulfate, aluminum chloride, aluminum nitrate, aluminum hydroxide, boehmite, pseudoboehmite, and pseudoboehmite.
5. The method for preparing the catalyst according to claim 2, characterized in that: The organic surfactant soft template is a long-chain asymmetric gemini quaternary ammonium salt surfactant;.
6. The method for preparing the catalyst according to claim 2, characterized in that: The molar composition of the alkali source, aluminum source, silicon source, gemini quaternary ammonium salt surfactant and organic amine auxiliary agent is: Na2O: Al2O3: SiO2: R: H2O: X is 1-30: 0.5-2: 100: 1-10: 1000-6000: 0.1-5, wherein R represents the gemini quaternary ammonium salt surfactant, and X represents the organic amine auxiliary agent.
7. The method for preparing the catalyst according to claim 2, characterized in that: The Zn salt is one or more of nitrate, sulfate, carbonate and halide, and the concentration of the metal element precursor solution is 0.01-50 mg / mL.
8. The use of a multi-level porous structure catalyst for n-octane aromatization as claimed in claim 1, characterized in that: Applied to the aromatization reaction of n-octane to produce aromatics.
9. The use according to claim 8, characterized in that: The n-octane aromatization multi-level porous structure catalyst is tableted, crushed, and sieved into particles of 40 to 60 meshes, and then the obtained particles are loaded into a continuous flow fixed bed reactor, and activated with nitrogen at 380 to 500° C. for half an hour before the reaction begins; the raw material n-octane is pumped into the fixed bed reactor with a horizontal flow pump, and the reaction is carried out under the conditions of an operating pressure of 0.1 MPa, a reaction temperature of 400 to 700° C., and a raw material liquid space velocity of 0.2 to 4.0 h; the outlet gas of the fixed bed reactor is monitored online by a gas chromatograph, and the gas phase products obtained mainly contain various light hydrocarbons and light aromatics of C1 to C5.
Citation Information
Cited By
Tungsten-containing hierarchical pore ZSM-5 zeolite molecular sieve and preparation method thereof
CN121990587A